Integrated Mine Planning and Geotechnical Engineering for Northeast BC Coal Mines (e0f0a96a-bfee-4155-90c5-5f00d9cd48ef) - Richard Dawson (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
Presentation Outline? Northeast BC Coal Fields Overview and History ?New mines and projects in development ?Design Issues for steeply dipping footwall slopes ?Design issues for angle-of-repose waste rock dumps